Serum selenium concentrations and risk of all-cause and heart disease mortality among individuals with type 2 diabetes. Issue 1 (19th October 2021) - Qiu, Zixin; Geng, Tingting; Wan, Zhenzhen; Lu, Qi; Guo, Jingyu; Liu, Liegang; Pan, An; Liu, Gang
ABSTRACT: Background: The impact of selenium status on the long-term health of people with type 2 diabetes (T2D) remains unclear. Objectives: To prospectively examine the association of serum selenium concentrations with all-cause and heart disease mortality among individuals with T2D. Methods: This analysis included 3199 adults with T2D from the third NHANES (NHANES III) and NHANES (2003–2004, 2011–2014). Mortality from heart disease and all causes was linked to National Death Index mortality data. Cox proportional hazard models were used to estimate HRs and 95% CIs. Results: The median (IQR) concentration of serum selenium was 127.0 (115.0, 139.1) µg/L. During an average 12.6-y follow-up, 1693 deaths were documented, including 425 heart disease deaths. Compared with participants in the lowest quartile of selenium, the multivariate-adjusted HRs (95% CIs) for participants in the highest quartile were 0.69 (0.54, 0.89) for all-cause mortality ( P -trend = 0.002) and 0.66 (0.45, 0.99) for heart disease mortality ( P -trend = 0.03). In addition, a linear dose–response relation between serum selenium (range: 89–182 µg/L) and mortality was observed. For per-unit increment in natural log-transformed serum selenium, there was a 64% lower risk of all-cause mortality and a 66% lower risk of heart disease mortality (both P < 0.05). Similar results were observed when stratifying by age, sex, race, smoking status, BMI, physical activity, diabetes duration, and HbA1c concentrations. Conclusions: Our study suggested that higher selenium concentration was associated with lower all-cause and heart disease mortality among individuals with T2D. More studies are needed to confirm these findings.